2015
DOI: 10.1111/ijfs.12819
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing on the antioxidant capacity and bioactive compounds in jellies from different blackberry cultivars

Abstract: Summary The effect of thermal processing and the berry cultivar has been the subject of several studies, to serve as a basis for the least possible loss of bioactive compounds and antioxidant capacity. In Brazil, there are numerous blackberry cultivars under cultivation, and in this context, the aim of this work was to study how the bioactive compound contents and antioxidant capacity of blackberry jelly were influenced by the cultivars (Guarani, Brazos, Comanche, Tupy, Cherokee, Caingangue and Choctaw). Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
1
23
1
Order By: Relevance
“…We believe that the high antioxidant capacity in blackberry jam is due to its higher content in phenolic compounds, and that in blueberry jam is due to the high content of anthocyanins. Several scientific reports corroborate our hypothesis; that is, that there is a close relation between the high antioxidant activity and the total phenolic compounds and anthocyanin content in berries (CARNEIRO et al, 2016;SEO et al, 2016;SOUZA et al, 2015).…”
Section: Bioactive Compounds and Antioxidant Activitysupporting
confidence: 83%
See 1 more Smart Citation
“…We believe that the high antioxidant capacity in blackberry jam is due to its higher content in phenolic compounds, and that in blueberry jam is due to the high content of anthocyanins. Several scientific reports corroborate our hypothesis; that is, that there is a close relation between the high antioxidant activity and the total phenolic compounds and anthocyanin content in berries (CARNEIRO et al, 2016;SEO et al, 2016;SOUZA et al, 2015).…”
Section: Bioactive Compounds and Antioxidant Activitysupporting
confidence: 83%
“…Ascorbic acid content was determined using the colorimetric method, using 2,4-dinitrophenylhydrazine, according to Strohecker and Henning (1967). The reading were carried out in a computerized Beckman 640B spectrophotometer, and the results were expressed in mg of ascorbic acid per 100g extract.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the jelly was conducted in the Plant Product Processing Laboratory. The jelly processing was based on previous work (Souza and others ,c ).…”
Section: Methodsmentioning
confidence: 99%
“…Hakala and others () have demonstrated that the strawberry cultivar has an influence on its composition, suggesting that different cultivars can influence the characteristics of the products obtained after processing. Recently in studies with different blackberry and raspberry cultivars it was demonstrated that the cultivar influenced the physicochemical, rheological, and sensory characteristics (Sønsteby and others ; Maro and others ; Souza and others ) as well as the antioxidant activity and bioactive compounds of jelly (Wang and Lin ; Souza and others ).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the vitamin C content, it appears that the Angulata and Pubences stand out for presenting the highest levels (75.44 mg/100 g and 72.87 mg/100 g, respectively). Tavarini et al (2008), Santos et al (2013) and Souza et al (2015) reported that the bioactive contents and total antioxidant capacity varies depending on the cultivar.…”
Section: Physalis Speciesmentioning
confidence: 99%